2022
DOI: 10.31389/jltc.107
|View full text |Cite
|
Sign up to set email alerts
|

Whose Outcome is it Anyway? Outcome and Brain Injury Case Management

Abstract: The acquired brain injury (ABI) literature highlights various factors that can prevent successful community rehabilitation and hinder good long-term outcomes. Brain injury case management is a service model with the potential to overcome these barriers within rehabilitation and longer-term care and support, but there is minimal research surrounding the effectiveness of case management in ABI.Objectives: This study aims to gain a better understanding of outcomes in brain injury case management and what facilita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…In addition to communication, studies also identi ed the importance of good working relationships between the client and case manager as a vital aspect of case management (25,36,39,42,49). Fitzsimmons (49) in their case study of 10 people with severe ABI, concluded that effective intervention was dependent upon the working relationship of case manager and client.…”
Section: Key Components Of Case Management Practicementioning
confidence: 99%
See 2 more Smart Citations
“…In addition to communication, studies also identi ed the importance of good working relationships between the client and case manager as a vital aspect of case management (25,36,39,42,49). Fitzsimmons (49) in their case study of 10 people with severe ABI, concluded that effective intervention was dependent upon the working relationship of case manager and client.…”
Section: Key Components Of Case Management Practicementioning
confidence: 99%
“…This ensures that family members are knowledgeable of brain injury, can make well-informed decisions, and act as an advocate for their loved one (54). However, in addition to providing information for family members, Lowry et al, (25) and Holloway et al, (24) contend that the case management role also involves working holistically to support the families of clients.…”
Section: Key Components Of Case Management Practicementioning
confidence: 99%
See 1 more Smart Citation
“…Rehabilitation is said to be a future-orientated process which looks to maximise function, physically, cognitively and socially, through restoration, compensation and adaptation while minimising medical complications and disability (Wressle, Oberg & Henriksson, 1999;Kischka, 2004;Gutenbrunner, Ward & Chamberlain, 2006;Meyer et al, 2011;Lowry et al, 2022). However, in severe brain injury, complete recovery is rare, and so, in many cases, despite often prolonged periods of rehabilitation, these people remain impaired and need significant care and support from others in the long term.…”
Section: Brain Injury Rehabilitationmentioning
confidence: 99%
“…Evaluation of the various models of CM for people with complex health conditions, such as brain injury, is lacking (including for people with traumatic brain injury [6,[10][11][12][13]. The evidence suggests that case management for people with brain injury is needed even though it represents a high cost.…”
Section: Introductionmentioning
confidence: 99%